(untitled) (Hong Kong Journal of Ophthalmology, 2016)
In recent years, optical coherence tomography has become an indispensable tool for ophthalmologists. In neuro-ophthalmology, this form of tomography is particularly useful for the structural documentation of peripapillary retinal nerve fiber layer thickness and optic nerve head morphology. The spectral-domain optical coherence tomography has advantages over the older, time-domain, optical coherence tomography and other instruments used to measure retinal nerve fiber layer thickness. Such other instruments for this purpose entail use of the confocal scanning laser ophthalmoscope and scanning laser polarimetry. Optical coherence tomography can aid diagnosis, disease monitoring and in some cases, give prognostic information about optic neuropathies. It is particularly useful for the diagnosis of functional visual loss, differentiation of optic neuropathy and maculopathy, and discriminating real disc swelling from pseudopapill- edema. Signal strength and movement artefacts affect the reliability of its images and measurements. The available technology is rapidly changing and it is important to keep up with latest developments so as to utilize this tool fully and interpret the findings correctly.